FEASIBILITY OF ALPHA TRANSFER STUDIES VIA (ALPHA,BE-8) REACTION AT HIGH-ENERGIES - Wozniak, G; Jelley, N; Cerny, J (1973)
Using a new Be8 identifier of high detection efficiency, we observed the (Be8) reaction on targets of B11, C12, and O16 at 65 MeV. Differential cross sections (1-60b/sr) were measured from c.m.=20°-80°. The only states strongly populated were those predicted to have large -structure amplitudes, implying that direct processes dominate at E=65 MeV. © 1973 The American Physical Society.